Citrobacter Amalonaticus Strain JB101에 의한 과염소산염과 질산염의 환원 : Kinetics 및 MBR을 이용한 처리 가능성 - 홍재화; 장명수; 이일수; 배재호; Hong, Jae-Wha; Jang, Myung-Su; Lee, Il-Su; Bae, Jae-Ho (Daehan hwan'gyeong gonghag hoeji, 2005)
This study was performed to evaluate the characteristics of the competition between two electron acceptors, perchlorate and nitrate, with Citrobacter Amalonaticus strain JB101. In addition, the applicability of membrane bioreactor(MBR) for perchlorate removal was evaluated. The maximum growth rate of strain JB101 on perchlorate and nitrate are 0.27 and 0.58 $hr^{-1}$, and maximum substrate utilization rates were 35.1 mg $ClO_4^-/g$ protein-day and 45.6 mg $NO_3^-/g$ protein-day, respectively. Nitrate was a competitive inhibitor for perchlorate, and strain JB101 prefer nitrate to perchlorate as electron acceptor. Complete removal of perchlorate could be achieved up to the surface leading rate of 4.6 g $ClO_4^-/m^2-day$ with the MBR fed with 20 mg $ClO_4^-/L$(HCMBR). When 5 mg/L of nitrate was added to the same influent, perchlorate removal efficiency decreased to 96.5%, while nitrate was completely removed. For the MBR fed with 0.7 mg/L of perchlorate (LCMBR), the maximum perchlorate removal efficiency was 100% up to the loading rate of 0.23 g $ClO_4^-/m^2-day$. Membrane fouling was found to be a problem at high leading rate for both MBRs. The acetate consumption ratio per perchlorate was $13.7{\sim}51.7\;e^-eq./e^-eq.$ in LCMBR, while the value was $2.5{\sim}3.6\;e^-eq./e^-eq.$ in HCMBR. This difference could be related to the acetate consumption with oxygen as electron acceptor. Therefore, the amount of acetate addition must be determined considering the concentrations of other electron acceptors in the influent. Citrobacter Amalonaticus strain JB101을 이용하여 과염소산염과 질산염이 동시에 존재할 때 두 전자수용체 간의 경쟁특성을 파악하고, MBR(membrane bioreactor)을 이용한 과염소산염 처리 가능성을 검토하였다. 과염소산 및 질산염에 대한 strain JB101의 비성장속도는 각각 0.27 및 0.58 $hr^{-1}$, 최대기질이용속도는 각각 35.1 mg $ClO_4^-/g$ protein-day 및 45.6 mg $NO_3^-/g$ protein-day이었다. 질산염은 과염소산염에 대한 경쟁적 저해제이었으며, strain JB101은 과염소산보다는 질산염을 전자수용체로 선호하였다. 유입 과염소산염 농도가 20 mg/L이였던 HCMBR에서는 막 면적당 부하 4.6 g $ClO_4^-/m^2-day$까지 과염소산염의 제거효율이 100%이었으나, 질산염 5 mg/L를 첨가하자 질산염은 완전히 제거되었으나 과염소산염 제거효율이 96.5%로 감소하였다. 유입 과염소산염 농도가 0.7 mg/L이였던 LCMBR에서는 부하 0.23 g $ClO_4^-/m^2-day$까지 과염소산염의 제거효율이 100%이었다. 두 MBR 모두 높은 부하에서는 막의 막힘현상이 문제로 제기되었다. 과염소산염에 대한 아세트산염 소모비는 LCMBR의 경우 $13.7{\sim}51.7$로 HCMBR의 $2.5{\sim}3.6$보다 높았으며, 이는 아세트산염이 산소를 전자수용체로 이용하여 소모되었기 때문이다. 따라서 전자공여체 첨가량은 유입수에 포함된 다른 전자수용체의 농도를 고려하여 결정하여야 한다.